Porous Material

The development of a porous body with specific compositional and structural characteristics addresses the limitations of conventional crosslinked polymer foams by enhancing ductility and resilience, making it suitable for diverse applications.

JP7667683B2Active Publication Date: 2025-04-23JSP CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021064030
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-05
Publication Date
2025-04-23
Estimated Expiration
2041-04-05

AI Technical Summary

Technical Problem

Conventional porous bodies based on crosslinked polymers, such as HIPE foams, lack sufficient ductility and resilience, making them inadequate for applications requiring large deformation without breaking.

Method used

A porous body made of a crosslinked polymer with a high content of acrylic monomer (40% by weight or more), a storage modulus of 10 kPa or more at 23°C, an apparent density between 20 kg/m³ and 250 kg/m³, a glass transition temperature of -30°C or higher, and a molecular weight between crosslinking points of 1.0×10⁴ or more.

Benefits of technology

The porous body achieves excellent resilience, softness, and ductility, enabling it to withstand large deformations while maintaining durability, making it suitable for various applications such as sound absorbing materials and cleaning products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007667683000005
    Figure 0007667683000005
  • Figure 0007667683000006
    Figure 0007667683000006
  • Figure 0007667683000007
    Figure 0007667683000007
Patent Text Reader

Abstract

To provide a porous body which is flexible, and is excellent in ductility and in restorability.SOLUTION: A porous body 1 contains a crosslinked polymer 11 obtained by crosslinking a polymer of an acrylic monomer and / or a styrenic monomer as a base material resin. The storage elastic modulus at 23°C of the porous body is 10 kPa or more and 2,000 kPa or less. The apparent density of the porous body 1 is 20 kg / m3 or more and 250 kg / m3 or less. The glass transition temperature of the crosslinked polymer 11 is -30°C or higher. The molecular weight between crosslinking points of the crosslinked polymer 11 is 1.0×104 or more and 12×104 or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous body based on a crosslinked polymer in which a polymer of an acrylic monomer and / or a styrene monomer is crosslinked, and more particularly to a porous body obtained by polymerization of a high internal phase emulsion (i.e., a HIPE foam). [Background technology]

[0002] Conventionally, a method has been known in which a water-in-oil type high internal phase emulsion (i.e., HIPE) is formed by incorporating a high ratio of an aqueous phase made of an aqueous liquid such as water in an organic phase containing a vinyl monomer, a crosslinking agent, an emulsifier, a polymerization initiator, etc., and the organic phase is polymerized in the emulsion to obtain a porous body made of a crosslinked polymer, called a HIPE foam or the like. This porous body becomes a polymer that reflects the dispersion form of the organic phase and the aqueous phase in the high internal phase emulsion and the dispersion form of the aqueous phase during polymerization, and has a bubble structure in which a large number of bubbles are uniformly present in the polymer, and also has an open bubble structure in which a large number of pores are formed to communicate between the bubbles. Therefore, the porous body is expected to be used for applications such as absorbents and separation materials.

[0003] For example, Patent Document 1 proposes a flexible HIPE foam (i.e., a porous body) with an adjusted density, glass transition temperature, and toughness index. According to Patent Document 1, such a porous body has excellent flexibility and is suitable for products such as wipes. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2003-514052 Summary of the Invention [Problem to be solved by the invention]

[0005] The application of porous bodies to a wide variety of applications, such as sound absorbing materials, vibration damping materials, cleaning products, etc., is being considered, and the development of porous bodies with excellent flexibility, ductility, and recovery properties is desired. For example, the conventional porous body described in Patent Document 1 has insufficient ductility, and therefore cannot be sufficiently elongated when subjected to a large deformation, and may break.

[0006] The present invention has been made in view of the above background, and aims to provide a porous body that is flexible and has excellent ductility as well as excellent restoring properties. [Means for solving the problem]

[0007] One aspect of the present invention is As a vinyl monomer A porous body having a crosslinked polymer obtained by crosslinking a polymer of an acrylic monomer and / or a styrene monomer as a base resin, The polymer is a polymer of the vinyl monomer having an acrylic monomer content of 40% by weight or more, The storage modulus of the porous body at 23°C is 10 kPa or more. 500 kPa or less, The apparent density of the porous body is 20 kg / m 3 More than 250kg / m 3 is as follows: The crosslinked polymer has a glass transition temperature of −30° C. or higher, The molecular weight between crosslinking points of the crosslinked polymer is 1.0×10 4 More than 12×10 4 The following is a porous body. Effect of the Invention

[0008] The storage modulus at 23° C., apparent density, glass transition temperature, and molecular weight between crosslinking points of the porous body are adjusted to fall within the above-mentioned ranges, and therefore the porous body has excellent restoring properties, is soft, yet has excellent ductility, and has excellent durability against large deformation. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a low-vacuum scanning electron microscope photograph of the porous body of Example 1. [Diagram 2]FIG. 2 is a DMA curve showing the relationship between the temperature T and the storage modulus E′ of the porous body of Example 1. [Diagram 3] FIG. 3 is a DMA curve showing the relationship between the temperature T and the loss tangent tan δ of the porous body of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Next, a preferred embodiment of the porous body will be described. In this specification, when a numerical value or a physical property value is enclosed before and after the symbol "~", the values ​​before and after the symbol are included. When a numerical value or a physical property value is expressed as a lower limit, it means that the value is equal to or greater than the numerical value or physical property value, and when a numerical value or a physical property value is expressed as an upper limit, it means that the value is equal to or less than the numerical value or physical property value. Furthermore, "parts by weight" and "% by weight" are essentially synonymous with "parts by mass" and "% by mass", respectively.

[0011] [Porous body] The porous body in this specification is a porous crosslinked polymer also called HIPE foam, polyHIPE foam, polyHIPE material, HIPE-derived foam material, high internal phase emulsion porous body, high internal phase emulsion foam, etc., and is obtained, for example, by polymerizing a monomer in a water-in-oil type high internal phase emulsion in which a high ratio of aqueous phase is contained in an organic phase. High internal phase emulsion is commonly called HIPE. In the following description, the porous body is appropriately called "HIPE foam". The porous body has an open-cell structure in which a large number of bubbles are present in the structure and a large number of through-holes are formed that connect adjacent bubbles.

[0012] More specifically, the HIPE foam has a large number of bubbles, uses a crosslinked polymer as a base resin, and has an open-cell structure. In general, soft HIPE foams are recognized as brittle materials with low durability against stresses such as friction, tension, and shear, but as disclosed herein, by adjusting the predetermined physical properties of the HIPE foam, a HIPE foam that is flexible and has excellent ductility and recovery properties can be obtained.

[0013] HIPE foam is a porous cross-linked polymer obtained by polymerizing a vinyl monomer (specifically, an acrylic monomer and / or a styrene monomer) in the presence of a cross-linking agent in a water-in-oil type high internal phase emulsion in which a high ratio of an aqueous phase is included in an organic phase. HIPE foam uses a cross-linked polymer containing a component derived from an acrylic monomer and / or a styrene monomer, obtained by polymerizing an acrylic monomer and / or a styrene monomer in a water-in-oil type high internal phase emulsion, as a base resin. HIPE foam specifically contains a component derived from an acrylic monomer and / or a styrene monomer in the polymer skeleton of the cross-linked polymer. In other words, HIPE foam uses a cross-linked polymer obtained by cross-linking a polymer of an acrylic monomer and / or a styrene monomer as a base resin.

[0014] Also, HIPE foam is a porous cured material obtained by curing a high internal phase emulsion, and the cell walls can be said to be composed of a crosslinked polymer (e.g., a vinyl-based crosslinked polymer). The cells can also be said to be pores. HIPE foam becomes a polymer (specifically, a porous crosslinked polymer) that reflects the dispersion form of the organic phase and the aqueous phase in the high internal phase emulsion and the dispersion shape of the aqueous phase (i.e., the dispersed phase) during polymerization.

[0015] In HIPE foams, the polymer is difficult to stretch during the manufacturing process, so that the polymer generally does not easily undergo molecular orientation and has little anisotropy. HIPE foams are distinct from foams that are stretched during manufacturing, such as foams obtained by extrusion foaming using an extruder, and foamed bead moldings obtained by foaming expandable resin beads and molding the foamed beads in a mold.

[0016] [Bubble structure] The HIPE foam is a porous body having an open cell structure as described above. As illustrated in FIG. 1, the HIPE foam 1 has a cell structure in which a large number of bubbles 13 are uniformly present in the crosslinked polymer 11 constituting the HIPE foam, and has an open cell structure in which a large number of through holes 14 are formed that penetrate the bubble walls 12 and communicate between adjacent bubbles. In FIG. 1, the bubbles 13 are the parts surrounded by the bubble walls 12. The through holes 14 are holes that penetrate the bubble walls 12 and communicate between adjacent bubbles 13. Specifically, the through holes 14 are holes that are formed in the bubble walls 12 and communicate between adjacent bubbles 13 across the bubble walls 12. The through holes 14 can also be called through windows or connecting holes.

[0017] From the viewpoint of further improving the restorability and strength of the HIPE foam, the average diameter of the bubbles of the HIPE foam is preferably 10 μm or more and 200 μm or less. The average diameter of the through-holes of the HIPE foam is generally 1 μm or more and 30 μm or less. Since the through-holes are holes that are generated in the bubble walls and communicate between the bubbles, the diameter of the through-holes is usually smaller than the diameter of the bubbles. The average diameter of the bubbles is the average value of the circle-equivalent diameters of the bubbles, and the circle-equivalent diameter of the bubbles is the diameter of a perfect circle having the same area as the area of ​​the bubbles in the cross section of the HIPE foam. The average diameter of the through-holes is the average value of the circle-equivalent diameters of the through-holes, and the circle-equivalent diameter of the through-holes is the diameter of a perfect circle having the same area as the area of ​​the through-holes in the cross section of the HIPE foam. The method for measuring the average diameter of the bubbles and the average diameter of the through-holes will be described later, but for example, they are measured by image analysis of the open-cell structure of the HIPE foam.

[0018] The average bubble size can be controlled by adjusting the droplet size of the aqueous phase (i.e., the dispersed phase) of the high internal phase emulsion in the manufacturing method of the HIPE foam described below. For example, by reducing the droplet size, the bubble size becomes finer, and the average bubble size in the HIPE foam can be easily adjusted to, for example, 200 μm or less.

[0019] The through-holes are formed by the breakage of the oil film due to the volumetric shrinkage of the polymer when the monomer is polymerized in the water-in-oil type high internal phase emulsion in the manufacturing method of HIPE foam described later. The oil film becomes the above-mentioned cell wall as the polymerization and crosslinking proceed. The average diameter of the through-holes can be controlled by adjusting the polymerization rate, the composition and viscosity of the organic phase, the stirring power density, etc. in the manufacturing method of HIPE foam described later.

[0020] [Storage modulus] The storage modulus of the HIPE foam at 23°C is 10 kPa or more and 2000 kPa or less. Since the storage modulus is in this range, the HIPE foam has moderate flexibility. For example, the storage modulus of the HIPE foam can be adjusted within the above range depending on the use of the porous body. From the viewpoint of further increasing the flexibility of the HIPE foam, the storage modulus of the HIPE foam at 23°C is preferably 1000 kPa or less, more preferably 600 kPa or less, even more preferably 500 kPa or less, and particularly preferably 300 kPa or less. In addition, from the viewpoint of increasing the rigidity of the HIPE foam while maintaining the flexibility of the HIPE foam, the storage modulus of the HIPE foam at 23°C is preferably 20 kPa or more, more preferably 30 kPa or more, and even more preferably 50 kPa or more. The method for measuring the storage modulus will be described later, but the storage modulus is measured by performing dynamic viscoelasticity measurement on the HIPE foam under the conditions of frequency: 1 Hz, load: 10 mN, and deformation mode: compression. The storage modulus is adjusted to within the above range by controlling the type and mixing ratio of the crosslinking agent, the type and mixing ratio of the monomer, the ratio of the organic phase to the aqueous phase, etc. in the manufacturing method of the HIPE foam described below. Furthermore, even when the porous body is used under a temperature condition lower than room temperature (e.g., 23° C.), from the viewpoint of the porous body easily exhibiting flexibility, the storage modulus at 0° C. is preferably 3000 kPa or less, more preferably 2500 kPa or less, and even more preferably 2000 kPa or less. From the viewpoint of ensuring the ductility and strength of the porous body, the storage modulus at 0° C. is preferably about 50 kPa or more, and more preferably 100 kPa or more. From the viewpoint of easily exhibiting good physical properties over a wide temperature range from room temperature to temperatures lower than room temperature, the ratio of the storage modulus at 0°C to the storage modulus at 23°C is preferably 0.005 or more and 0.5 or less, and more preferably 0.01 or more and 0.3 or less.

[0021] [Apparent Density] The apparent density of HIPE foam is 20kg / m 3 More than 250kg / m 3 The apparent density is within this range, so that the HIPE foam has excellent resilience and ductility. If the apparent density is too low, the resilience tends to decrease, and if the apparent density is too high, the ductility tends to decrease. For example, the apparent density of the HIPE foam can be adjusted within the above range depending on the application of the porous body. From the viewpoint of further improving the resilience of the HIPE foam, the apparent density of the HIPE foam is preferably 30 kg / m or less. 3 It is preferable that the saturation temperature is 35 kg / m or more. 3 More preferably, it is 40 kg / m or more. 3 More preferably, it is 50 kg / m or more. 3 It is particularly preferable that the apparent density of the HIPE foam is 200 kg / m or more, from the viewpoint of obtaining a lightweight HIPE foam and further improving the ductility of the HIPE foam. 3 It is preferable that the thickness is less than 150 kg / m 3 It is more preferable that:

[0022] The apparent density ρ of a HIPE foam is calculated by dividing the weight by the volume.

[0023] The apparent density ρ of the HIPE foam is adjusted to be within the above range by adjusting the ratio of the total amount of vinyl monomer, crosslinking agent, emulsifier, and polymerization initiator to the amount of aqueous phase (specifically, aqueous liquid) in the manufacturing method of the HIPE foam described below.

[0024] [Molecular weight between crosslinking points] The molecular weight Mc between crosslinking points is an index of the degree of crosslinking of the crosslinked polymer constituting the HIPE foam. The molecular weight between crosslinking points of the crosslinked polymer is 1.0×10 4 More than 12×10 4 or less. Since the molecular weight between crosslinking points is within this range, the HIPE foam has excellent ductility and recovery. If the molecular weight between crosslinking points is too low, the degree of crosslinking becomes too high, and the ductility of the HIPE foam decreases, whereas if the molecular weight between crosslinking points is too high, the degree of crosslinking becomes too low, and the recovery of the HIPE foam tends to decrease. For example, the glass transition temperature of the HIPE foam can be adjusted within the above range depending on the application of the porous body. From the viewpoint of further improving the ductility of the HIPE foam, the molecular weight between crosslinking points of the crosslinked polymer is 2.0×10 4 More preferably, it is 2.5×10 4 More preferably, it is 3.0×10 or more. 4 From the viewpoint of further improving the restoring property of the HIPE foam, the molecular weight between crosslinking points of the crosslinked polymer is preferably 10×10 4 It is preferable that the value is less than 8.0×10 4 More preferably, it is 6.0×10 or less. 4 It is even more preferable that:

[0025] The molecular weight Mc between crosslinking points of the crosslinked polymer that constitutes the HIPE foam is measured as follows. Dynamic mechanical analysis (DMA) is performed on the HIPE foam under the conditions of frequency: 1 Hz, load: 10 mN, and deformation mode: compression. At this time, as the temperature rises, the crosslinked polymer that constitutes the HIPE foam transitions from a glassy state to a rubbery state, so in the DMA curve obtained by plotting temperature on the horizontal axis and storage modulus E' on the vertical axis, the storage modulus E' drops sharply at the glass transition temperature Tg (see Figure 2). After that, the DMA curve shows a plateau region (rubber-like flat section). In this plateau region, E' is proportional to temperature, so the molecular weight Mc between crosslinking points can be calculated from the following formula (I). Mc = 2(1 + μ)ρRT / E' (I)

[0026] In formula (I), μ is the Poisson's ratio, μ = 0.5. ρ is the apparent density of the HIPE foam, kg / m 3 , R is the gas constant: 8.314 J / K / mol. T and E' are the temperature (unit: K) and storage modulus (unit: kPa) at an arbitrary point on the rubber-like flat part, respectively. T and E' are values ​​measured on the rubber-like flat part. From the viewpoint of being able to properly calculate the molecular weight Mc between crosslinking points, it is preferable to measure the above E' in the temperature range of Tg+50°C to Tg+80°C (where Tg is the glass transition temperature of the crosslinked polymer constituting the HIPE foam). The Poisson's ratio is a value inherent to a material, and is a value obtained by dividing the strain generated in the vertical direction by the strain generated in the parallel direction when stress is applied to an object, and multiplying this by -1. Theoretically, the Poisson's ratio takes values ​​in the range of -1 to 0.5, and when this value is negative, it means that when it is crushed in the vertical direction, it is also crushed in the horizontal direction. Conversely, when it is positive, it means that when it is crushed in the vertical direction, it stretches in the horizontal direction. Under the measurement conditions for the dynamic viscoelastic analysis described above, the distortion occurring in the cross-linked polymer constituting the HIPE foam is extremely small, and it can be assumed that no change in volume occurs. Therefore, the storage modulus E' and the molecular weight between cross-linking points Mc are calculated under a constant volume condition, i.e., a Poisson's ratio of 0.5.

[0027] The molecular weight Mc between crosslinking points of the crosslinked polymer constituting the HIPE foam can be reduced by adding a crosslinking agent in the manufacturing method of the HIPE foam described below, and is adjusted to the above range by adjusting the type and mixing ratio of the crosslinking agent, the type and mixing ratio of the monomer, etc. described below.

[0028] [Glass transition temperature Tg] The glass transition temperature Tg of the crosslinked polymer constituting the HIPE foam is -30°C or higher. With Tg in this range, the HIPE foam has excellent ductility. If Tg is too low, the ductility tends to decrease. For example, the Tg of the HIPE foam can be adjusted within the above range according to the ductility required for the application of the porous body. From the viewpoint of further improving the ductility of the HIPE foam, the glass transition temperature of the crosslinked polymer is preferably -20°C or higher, and more preferably -10°C or higher. In addition, from the viewpoint of further improving the flexibility of the HIPE foam at room temperature (specifically, 23°C), the glass transition temperature is preferably 30°C or lower, more preferably 20°C or lower, and even more preferably 10°C or lower.

[0029] The glass transition temperature Tg of the crosslinked polymer that constitutes the HIPE foam is measured by differential scanning calorimetry (DSC) analysis based on JIS K7121:1987. The glass transition temperature is the midpoint glass transition temperature of the DSC curve. The condition of the test specimen is adjusted as follows: (3) The glass transition temperature is measured after a certain heat treatment.

[0030] The glass transition temperature Tg of the crosslinked polymer constituting the HIPE foam is adjusted to be within the above range by adjusting the type and blending ratio of the vinyl monomer, the type and blending ratio of the crosslinking agent, etc. in the manufacturing method of the HIPE foam described below.

[0031] The maximum value of the loss tangent tanδ in the temperature-loss tangent tanδ curve of the HIPE foam is preferably 0.8 or more and 1.6 or less. In this case, the ductility and recovery of the HIPE foam are further improved. The loss tangent tanδ is measured by subjecting the HIPE foam to dynamic viscoelasticity measurement under the conditions of frequency: 1 Hz, load: 10 mN, and deformation mode: compression. In the dynamic viscoelasticity measurement, the heating rate is preferably 10°C / min and the temperature range is preferably -100 to 120°C. From the viewpoint of forming a more uniform crosslinked structure in the crosslinked polymer and further improving the ductility of the HIPE foam, the maximum value of the loss tangent tan δ of the HIPE foam is more preferably 0.9 or more, and even more preferably 1.0 or more. Moreover, from the viewpoint of more reliably forming a crosslinked structure and making it easier to improve the restoring property of the HIPE foam, the maximum value of the loss tangent tan δ of the HIPE foam is more preferably 1.5 or less, and even more preferably 1.4 or less.

[0032] In addition, the half-width of the tan δ peak, which indicates the maximum value of the loss tangent tan δ in the temperature-loss tangent tan δ curve, is preferably 10°C or more and 25°C or less. In this case, the ductility and flexibility of the HIPE foam are further improved. From the viewpoint of forming a more uniform crosslinked structure in the crosslinked polymer and further improving the ductility of the HIPE foam, the half-width of the tan δ peak is more preferably 23°C or less, and even more preferably 20°C or less. In addition, from the viewpoint of easily increasing the ductility of the HIPE foam while maintaining the restorability of the HIPE foam, the half-width of the tan δ peak is preferably 12°C or more, and more preferably 14°C or more.

[0033] The method for measuring the maximum value of loss tangent tan δ and the half-value width of the tan δ peak will be described in detail later, but they are measured by dynamic viscoelasticity measurement (that is, DMA). The half-width H of the tan δ peak is the full width at half maximum in the DMA curve, and means the temperature width of the tan δ peak in the DMA curve at the position showing the value of the loss tangent tan δ that is half (1 / 2) of the maximum value of the tan δ peak (i.e., the peak top value in the DMA curve expressed as the relationship between the temperature T (unit: °C) and the loss tangent tan δ) (see Figure 3). In general, when the maximum value of the loss tangent tanδ is large, the half-width of the corresponding tanδ peak tends to be small. Even if the temperature around the HIPE foam during use is lower than the Tg of the crosslinked polymer but close to the Tg of the crosslinked polymer, it is preferable that the maximum value of the loss tangent tanδ is large and the half-width of the tanδ peak is small, from the viewpoint of making the HIPE foam flexible. The maximum value of the loss tangent tanδ and the half-value width of the tanδ peak are adjusted to the above ranges by controlling the type and mixing ratio of the crosslinking agent described below, the type and mixing ratio of the monomer, etc., in the manufacturing method of the HIPE foam described below. For example, by appropriately containing a soft crosslinking agent component derived from a soft crosslinking agent having a relatively long molecular chain described below in the crosslinked polymer, it is possible to increase the maximum value of the loss tangent tanδ and reduce the half-value width of the tanδ peak while keeping the molecular weight between crosslinking points within a predetermined range.

[0034] The recovery rate of the HIPE foam after 25% compression at 23°C is preferably 90% or more. In this case, the recovery property of the HIPE foam is sufficiently high, and the HIPE foam is more suitable for applications such as sound absorbing materials, vibration damping materials, cleaning supplies, cushioning materials, toys, etc. From the same viewpoint, the recovery rate of the HIPE foam after 25% compression at 23°C is more preferably 95% or more, and even more preferably 98% or more. The upper limit of the recovery rate of the HIPE foam after 25% compression at 23°C is 100%. The recovery rate after 25% compression is measured in accordance with JIS K6767:1999. Specifically, as described later, the HIPE foam is left in a 25% compressed state for 22 hours, then decompressed, and the thickness is measured 30 minutes after decompression. Based on the measurement results, the recovery rate is calculated from the calculation formula: thickness 30 minutes after decompression / thickness before compression x 100. The recovery rate after 25% compression at 23°C is adjusted to be within the above range by controlling the type and mixing ratio of the crosslinking agent, the type and mixing ratio of the monomer, the ratio of the organic phase to the aqueous phase, etc., in the manufacturing method of the HIPE foam described below.

[0035] The tensile breaking elongation of the HIPE foam at 23°C is preferably 70% or more. In this case, the ductility of the HIPE foam is sufficiently high, and the HIPE foam is more suitable for applications such as sound absorbing materials, vibration damping materials, cleaning supplies, cushioning materials, toys, etc. From the same viewpoint, the tensile breaking elongation of the HIPE foam at 23°C is more preferably 75% or more, even more preferably 80% or more, and particularly preferably 100% or more. From the viewpoint of easily increasing the restorability of the HIPE foam while maintaining the ductility of the HIPE foam, the tensile breaking elongation of the HIPE foam at 23°C is preferably 500% or less, more preferably 400% or less. The method for measuring the tensile breaking elongation at 23°C will be described later, but it is a tensile breaking strain measured by performing a tensile test on a test piece punched into a 1A shape of JIS K7161-2:2014 at a tensile speed of 100 mm / min based on JIS K7161-2:2014. The tensile elongation at break at 23°C is adjusted to be within the above range by controlling the type and mixing ratio of the crosslinking agent, the type and mixing ratio of the monomer, the ratio of the organic phase to the aqueous phase, etc. in the manufacturing method of the HIPE foam described below.

[0036] The breaking energy per unit weight of the HIPE foam is preferably 50 mJ / g or more. In this case, the strength of the HIPE foam is sufficiently high, and the HIPE foam is more suitable for applications such as sound absorbing materials, vibration damping materials, cleaning supplies, cushioning materials, toys, etc. From the same viewpoint, the breaking energy per unit weight of the HIPE foam is more preferably 60 mJ / g or more, even more preferably 80 mJ / g or more, and even more preferably 100 mJ / g or more. The breaking energy per unit weight of the HIPE foam is not limited as long as it is within a range in which the intended object of the present invention is achieved, but is preferably approximately 3000 mJ / g or less, and more preferably 2500 mJ / g or less. The method for measuring the breaking energy per unit weight will be described later. The breaking energy per unit weight is adjusted to the above range by controlling the type and blending ratio of the crosslinking agent, the type and blending ratio of the monomer, the ratio of the organic phase to the aqueous phase, etc., in the manufacturing method of the HIPE foam described later.

[0037] [Components] The crosslinked polymer constituting the HIPE foam is specifically a polymer of a monofunctional vinyl monomer and a crosslinking agent, and has a component derived from the monofunctional vinyl monomer. In this specification, the vinyl monomer is a styrene monomer, an acrylic monomer, etc. As the vinyl monomer, an acrylic monomer and / or a styrene monomer can be used.

[0038] The crosslinked polymer is preferably composed of a polymer of a vinyl monomer including an acrylic monomer and / or a styrene monomer, and a crosslinking agent. Specifically, the crosslinked polymer preferably has an acrylic monomer component and / or a styrene monomer component in the polymer skeleton, and also has a crosslinking agent component described below. In this case, the balance between the toughness and rigidity of the HIPE foam is better. The styrene monomer component means a structural unit derived from a styrene monomer in the crosslinked polymer, and the acrylic monomer component means a structural unit derived from an acrylic monomer in the crosslinked polymer. From the viewpoint of facilitating the production of a HIPE foam having desired physical properties, the content of the acrylic monomer component and / or the styrene monomer component in the crosslinked polymer is preferably 50% by weight or more, more preferably 60% by weight or more, and even more preferably 70% by weight or more. From the same viewpoint, the content of the acrylic monomer component and / or the styrene monomer component in the crosslinked polymer is preferably 95% by weight or less, and more preferably 90% by weight or less.

[0039] Examples of the styrene-based monomer include styrene compounds such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-ethylstyrene, 2,4-dimethylstyrene, p-methoxystyrene, pn-butylstyrene, pt-butylstyrene, divinylbenzene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,4,6-tribromostyrene, styrenesulfonic acid, and sodium styrenesulfonate. Examples of the acrylic monomer include acrylic esters such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hydroxyethyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, isobornyl acrylate, dicyclopentanyl acrylate, and adamantyl acrylate; and methacrylic esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, isobornyl methacrylate, dicyclopentanyl methacrylate, and adamantyl methacrylate. Examples of the acrylic monomer also include acrylamide, methacrylamide, and acrylonitrile.

[0040] The crosslinked polymer may be composed of a copolymer of a (meth)acrylic acid ester and a crosslinking agent, but is preferably composed of a copolymer of a styrene-based monomer, a vinyl-based monomer including a (meth)acrylic acid ester, and a crosslinking agent. In other words, the crosslinked polymer preferably has a styrene-based monomer and a component (i.e., a structural unit) derived from a (meth)acrylic acid ester in the polymer skeleton. In this case, it is easy to obtain a HIPE foam composed of a crosslinked polymer having desired physical properties. Since the crosslinked polymer is a crosslinked polymer, it has a component (i.e., a structural unit) derived from a crosslinking agent in the polymer skeleton. The (meth)acrylic acid ester is an ester of (meth)acrylic acid and an alcohol, and is preferably an ester of (meth)acrylic acid and an alcohol having 1 to 20 carbon atoms.

[0041] The crosslinked polymer is a crosslinked polymer obtained by crosslinking a copolymer of an acrylic monomer and a styrene monomer, and the acrylic monomer is preferably an ester of (meth)acrylic acid and an alcohol having 1 to 20 carbon atoms. In this case, it is easy to obtain a HIPE foam having desired physical properties, and it is easy to adjust the glass transition temperature of the crosslinked polymer to a desired range.

[0042] When the vinyl monomer contains an acrylic monomer, the content of the acrylic monomer in the vinyl monomer is preferably 40% by weight or more, more preferably 50% by weight or more, and even more preferably 60% by weight or more. The weight ratio of the acrylic monomer to the styrene monomer is preferably 40:60 to 90:10, and more preferably 50:50 to 80:20. In this case, the effects of reducing the production cost and facilitating the adjustment to the desired physical properties can be obtained. Incidentally, (meth)acrylic acid means acrylic acid and / or methacrylic acid.

[0043] In addition, from the viewpoint of being able to stably obtain a crosslinked polymer having excellent physical properties and a desired glass transition temperature, the number of carbon atoms in the hydrocarbon group constituting the (meth)acrylic acid ester is preferably 1 to 20, more preferably 2 to 18, even more preferably 3 to 16, and even more preferably 4 to 12. The hydrocarbon group is more preferably an alkyl group. The hydrocarbon group may be either cyclic or non-cyclic. Among these, it is preferable to use an acrylic acid ester having a hydrocarbon group with a carbon number of 3 to 10, more preferably 2-ethylhexyl acrylate and / or butyl acrylate, and even more preferably butyl acrylate. For example, by using 2-ethylhexyl acrylate or butyl acrylate, the glass transition temperature of the crosslinked polymer can be easily lowered.

[0044] A crosslinked polymer has a crosslinked structure and contains a crosslinking agent component. The crosslinking agent component is a structural unit derived from the crosslinking agent in the crosslinked polymer. The crosslinking agent is a compound that crosslinks (bonds) between the polymer chains that make up the polymer, forming a crosslinked structure in the polymer. As the crosslinking agent, for example, a vinyl-based compound having at least two functional groups selected from vinyl and isopropenyl groups in the molecule is used. When the crosslinked polymer contains a predetermined amount of a crosslinking agent component, the rigidity and toughness of the crosslinked polymer can be increased, and the value of the molecular weight between crosslinking points of the crosslinked polymer can be reduced. The vinyl-based compound also includes a compound containing a vinyl group and / or an isopropenyl group in the structure of the functional group, such as an acryloyl group or a methacryloyl group. From the viewpoint of stably polymerizing the crosslinking agent, the number of functional groups in the vinyl-based compound is preferably 6 or less, more preferably 5 or less, and more preferably 4 or less. In addition, from the viewpoint of making it easier to increase the toughness of the crosslinked polymer, the crosslinking agent preferably has functional groups at least at both ends of the molecule, and more preferably has functional groups only at both ends of the molecule.

[0045] The crosslinked polymer may contain one type of crosslinking agent component produced using one type of crosslinking agent, for example. However, it is preferable to contain a hard crosslinking agent component derived from a hard crosslinking agent having a relatively short molecular chain and a soft crosslinking agent component derived from a soft crosslinking agent having a relatively long molecular chain, since it is easy to increase the toughness of the crosslinked polymer while increasing the rigidity of the crosslinked polymer. In this case, it is easy to adjust the molecular weight Mc between crosslinking points of the crosslinked polymer constituting the HIPE foam, the storage modulus at a temperature of 23°C, the maximum value of the loss tangent tanδ, etc., within the above range. In addition, excessive embrittlement of the HIPE foam is easily suppressed, and even when a HIPE foam having a complex shape, such as having a thin portion, is produced, it is possible to suppress the occurrence of chipping in the HIPE foam. The hard crosslinking agent can also be called the first crosslinking agent, and the soft crosslinking agent can also be called the second crosslinking agent.

[0046] The hard crosslinking agent (i.e., the first crosslinking agent) is preferably a vinyl compound having a functional group equivalent of 130 g / eq or less. Since such a hard crosslinking agent has a relatively short molecular chain, it is considered that the mobility of the polymer molecular chain is reduced by copolymerizing with a vinyl monomer. The use of a hard crosslinking agent makes it easier to increase the rigidity of the HIPE foam. From the viewpoint of facilitating the production of the HIPE foam, the lower limit of the functional group equivalent of the hard crosslinking agent is preferably 30 g / eq, more preferably 40 g / eq, even more preferably 50 g / eq, and even more preferably 60 g / eq. The upper limit of the functional group equivalent of the hard crosslinking agent is preferably 120 g / eq. The functional group equivalent of the hard crosslinking agent means the molar mass of the hard crosslinking agent per functional group (specifically, an alkenyl group such as a vinyl group or an isopropenyl group), and the unit of the functional group equivalent can also be expressed as [g / mol].

[0047] The soft crosslinking agent (i.e., the second crosslinking agent) is preferably a vinyl compound having a functional group equivalent of more than 130 g / eq and not more than 5000 g / eq. Since such a soft crosslinking agent has a relatively long molecular chain, it is considered that it can crosslink between polymer molecular chains by copolymerizing with a vinyl monomer without significantly reducing the mobility of the polymer molecular chain. The use of a soft crosslinking agent makes it easy to increase the toughness of the HIPE foam. From the viewpoint of easy handling, the upper limit of the functional group equivalent of the soft crosslinking agent is preferably 5000 g / eq, more preferably 4000 g / eq, and even more preferably 3000 g / eq. In addition, the lower limit of the functional group equivalent of the soft crosslinking agent is preferably 150 g / eq, more preferably 180 g / eq, and even more preferably 200 g / eq. The functional group equivalent of a soft crosslinking agent means the molar mass of the soft crosslinking agent per functional group (specifically, an alkenyl group such as a vinyl group or an isopropenyl group), and the unit of functional group equivalent can also be expressed as [g / mol].

[0048] From the viewpoint of facilitating the enhancement of toughness and rigidity of the HIPE foam and facilitating the adjustment of the maximum value of the loss tangent tanδ and the half-width of the tanδ peak to the above ranges, the functional group equivalent of the soft crosslinking agent is preferably 60 g / eq or more larger than the functional group equivalent of the hard crosslinking agent, more preferably 80 g / eq or more, even more preferably 100 g / eq or more, and even more preferably 120 g / eq or more. In other words, the difference between the functional group equivalent of the soft crosslinking agent and the functional group equivalent of the hard crosslinking agent is preferably 60 g / eq or more, more preferably 80 g / eq or more, even more preferably 100 g / eq or more, and even more preferably 120 g / eq or more. In addition, from the viewpoint of improving the polymerization stability and stably obtaining a porous body excellent in rigidity and toughness, the difference between the functional group equivalent of the soft crosslinking agent and the functional group equivalent of the hard crosslinking agent is preferably 3000 g / eq or less, more preferably 2000 g / eq or less, and even more preferably 1000 g / eq or less. When two or more types of hard crosslinking agents are used, the weight average value of the functional group equivalents of all the hard crosslinking agents is calculated, and this value is taken as the functional group equivalent of the hard crosslinking agent. Similarly, when two or more types of soft crosslinking agents are used, the weight average value of the functional group equivalents of all the soft crosslinking agents is calculated, and this value is taken as the functional group equivalent of the soft crosslinking agent.

[0049] Examples of vinyl compounds used as hard crosslinking agents include vinyl compounds such as divinylbenzene, triallyl isocyanurate, and esters of polyhydric alcohols and (meth)acrylic acid. Examples of esters of polyhydric alcohols and (meth)acrylic acid include vinyl compounds such as butanediol (meth)acrylates such as butanediol diacrylate, trimethylolpropane (meth)acrylates such as trimethylolpropane triacrylate, hexanediol (meth)acrylates such as hexanediol diacrylate, and pentaerythritol (meth)acrylates such as pentaerythritol tetraacrylate. However, the number of functional groups in the hard crosslinking agent is two or more. The functional groups are preferably vinyl groups and / or isopropenyl groups. The hard crosslinking agent may be one type or two or more types. That is, the hard crosslinking agent component constituting the crosslinked polymer may be one type or two or more types. From the viewpoint of making it easier to adjust the rigidity of the HIPE foam, it is preferable to use divinylbenzene and / or butanediol diacrylate as the hard crosslinking agent.

[0050] Examples of vinyl compounds used as soft crosslinking agents include esters of polyhydric alcohols and (meth)acrylic acid, esters of polyether glycols and (meth)acrylic acid, esters of urethane oligomers and (meth)acrylic acid, esters of epoxy oligomers and (meth)acrylic acid, and (meth)acrylic-modified silicones. More specifically, the vinyl compounds include nonanediol (meth)acrylates such as nonanediol diacrylate; decanediol (meth)acrylates such as decanediol diacrylate; polyethylene glycol (meth)acrylates such as polyethylene glycol diacrylate; polypropylene (meth)acrylates such as polypropylene glycol diacrylate; polytetramethylene glycol (meth)acrylates such as polytetramethylene glycol diacrylate; polyglycerin (meth)acrylates such as polyglycerin diacrylate; urethane (meth)acrylates such as urethane diacrylate; epoxy (meth)acrylates such as epoxy diacrylate; polyester (meth)acrylates such as polyester diacrylate; (meth)acrylic modified silicones such as silicones modified at both ends with (meth)acrylic; caprolactone modified isocyanurates such as caprolactone modified tris isocyanurates; ethoxylated bisphenol A (meth)acrylates such as ethoxylated bisphenol A dimethacrylate. However, the number of functional groups in the soft crosslinking agent is two or more. The functional group is preferably a vinyl group and / or an isopropenyl group. The soft crosslinking agent may be one type or two or more types. That is, the soft crosslinking agent component constituting the crosslinked polymer may be one type or two or more types. From the viewpoint of making it easier to adjust the toughness of the HIPE foam, it is preferable to use polyethylene glycol di(meth)acrylate as the soft crosslinking agent. The number of repeating structural units derived from ethylene glycol in the polyethylene glycol di(meth)acrylate is preferably 3 to 23.Furthermore, from the viewpoint of further increasing the ductility and strength of the HIPE foam, it is preferable to use a soft crosslinking agent having a functional group equivalent of 500 g / eq or more and 3000 g / eq or less, and it is more preferable to use a urethane (meth)acrylate and / or an epoxy (meth)acrylate as the soft crosslinking agent.

[0051] Table 1 shows the molecular weights of representative crosslinking agents and the molecular weights per functional group (i.e., functional group equivalents).

[0052] [Table 1]

[0053] When the crosslinked polymer is composed of at least an acrylic monomer, a styrene monomer, and a copolymer of a crosslinking agent, from the viewpoint of easily adjusting the molecular weight Mc between crosslinking points and the storage modulus at a temperature of 23 ° C. to the above range, and from the viewpoint of a better balance between the toughness and rigidity of the HIPE foam, the content of the acrylic monomer component in the crosslinked polymer is preferably 30 parts by weight or more and 85 parts by weight or less, more preferably 40 parts by weight or more and 75 parts by weight or less, and even more preferably 45 parts by weight or more and 65 parts by weight or less, relative to 100 parts by weight of the total of the vinyl monomer component and the crosslinking agent component constituting the crosslinked polymer. From the same viewpoint, the content of the styrene monomer component in the crosslinked polymer is preferably 10 parts by weight or more and 50 parts by weight or less, more preferably 15 parts by weight or more and 45 parts by weight or less, and even more preferably 20 parts by weight or more and 40 parts by weight or less, relative to 100 parts by weight of the total of the vinyl monomer component and the crosslinking agent component constituting the crosslinked polymer. As the acrylic monomer, it is preferable to use an acrylic acid ester having a hydrocarbon group with 3 to 10 carbon atoms, and the content of the acrylic acid ester having a hydrocarbon group with 3 to 10 carbon atoms in the acrylic monomer is preferably 50% by weight or more, more preferably 80% by weight or more, and even more preferably 90% by weight or more. Moreover, as the acrylic ester having a hydrocarbon group with 3 to 10 carbon atoms, 2-ethylhexyl acrylate and / or butyl acrylate is / are preferred, and butyl acrylate is / are more preferred.

[0054] From the viewpoint of making it easier to adjust the molecular weight between crosslinking points Mc and the storage modulus at a temperature of 23°C of the crosslinked polymer within the above-mentioned ranges, the content of the crosslinking agent component in the crosslinked polymer (specifically, the total content of the soft-based crosslinking agent component and the hard-based crosslinking agent component in the crosslinked polymer) is preferably 5 parts by weight or more and 40 parts by weight or less, more preferably 6 parts by weight or more and 35 parts by weight or less, and even more preferably 10 parts by weight or more and 30 parts by weight or less, relative to 100 parts by weight of the total of the vinyl-based monomer components and the crosslinking agent components constituting the crosslinked polymer. In addition, when the crosslinked polymer contains a crosslinking agent component having a functional group equivalent of 500 g / eq or more and 3000 g / eq or less, the content of the crosslinking agent component having a functional group equivalent of 500 g / eq or more and 3000 g / eq or less in the crosslinked polymer is preferably 20 parts by weight or more and 40 parts by weight or less per 100 parts by weight of the total of the vinyl monomer component and the crosslinking agent component constituting the crosslinked polymer. The crosslinking agent component having a functional group equivalent of 500 g / eq or more and 3000 g / eq or less corresponds to a soft crosslinking agent.

[0055] In the case where the crosslinked polymer contains a hard crosslinking agent component and a soft crosslinking agent component, from the viewpoint of easily increasing the rigidity of the HIPE foam and easily adjusting the molecular weight between crosslinking points Mc and the storage modulus at a temperature of 23 ° C. to the above range, the content of the hard crosslinking agent component in the crosslinked polymer is preferably 1 part by weight or more and 10 parts by weight or less, more preferably 2 parts by weight or more and 6 parts by weight or less, and even more preferably 2 parts by weight or more and 5 parts by weight or less, relative to 100 parts by weight of the total of the vinyl monomer component and the crosslinking agent component constituting the crosslinked polymer. In addition, from the viewpoint of easily adjusting the molecular weight between crosslinking points Mc and the storage modulus at a temperature of 23 ° C. to the above range while suppressing excessive embrittlement of the HIPE foam, the content of the soft crosslinking agent component in the crosslinked polymer is preferably 3 parts by weight or more and 40 parts by weight or less, more preferably 5 parts by weight or more and 35 parts by weight or less, and even more preferably 8 parts by weight or more and 30 parts by weight or less, relative to 100 parts by weight of the total of the vinyl monomer component and the crosslinking agent component constituting the crosslinked polymer. From the viewpoint of easily adjusting the molecular weight between crosslinking points Mc, the storage modulus at a temperature of 23°C, the maximum value of the loss tangent tanδ, and the like within the above-mentioned ranges, the weight ratio of the hard crosslinking agent component to the soft crosslinking agent component is preferably 0.05 or more and 1.0 or less, more preferably 0.06 or more and 0.6 or less, even more preferably 0.08 or more and 0.5 or less, and particularly preferably 0.1 or more and 0.4 or less.

[0056] [Manufacturing method] HIPE foams are produced by polymerizing high internal phase emulsions, specifically, by polymerizing water-in-oil type high internal phase emulsions, in which the organic phase is a continuous phase containing vinyl monomers, crosslinking agents, emulsifiers, polymerization initiators, etc., and the aqueous phase is a dispersed phase containing water, such as deionized water.

[0057] More preferred embodiments (specifically, the first and second embodiments) of the method for producing a HIPE foam (that is, a porous body) are as follows. A first aspect is a method for producing a porous body by forming a water-in-oil type high internal phase emulsion in which an aqueous phase containing water is encapsulated in an organic phase containing an acrylic monomer and / or a styrene monomer, a crosslinking agent, an emulsifier, and a polymerization initiator, and polymerizing the acrylic monomer and / or the styrene monomer in the emulsion, the crosslinking agent is a vinyl-based compound having at least two functional groups selected from a vinyl group and an isopropenyl group in the molecule, and includes a first crosslinking agent having a functional group equivalent of 130 g / eq or less, and a second crosslinking agent having a functional group equivalent of more than 130 g / eq and 5000 g / eq or less; the amount of the crosslinking agent added is 5 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the total of the acrylic monomer, the styrene monomer, and the crosslinking agent; the amount of the second crosslinking agent added is 3 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the total of the acrylic monomer, the styrene monomer, and the crosslinking agent; The method for producing a porous body includes a ratio of the weight of the first crosslinking agent to the weight of the second crosslinking agent of 0.05 or more and 1.0 or less.

[0058] A second aspect is a method for producing a porous body by forming a water-in-oil type high internal phase emulsion in which an aqueous phase containing water is encapsulated in an organic phase containing an acrylic monomer and / or a styrene monomer, a crosslinking agent, an emulsifier, and a polymerization initiator, and polymerizing the acrylic monomer and / or the styrene monomer in the emulsion, comprising the steps of: The crosslinking agent is a vinyl-based compound having at least two functional groups selected from a vinyl group and an isopropenyl group in the molecule, and has a functional group equivalent of 500 g / eq or more and 3000 g / eq or less, A method for producing a porous body, wherein the amount of the crosslinking agent added is 20 parts by weight or more and 40 parts by weight or less per 100 parts by weight of the total of the acrylic monomer, the styrene monomer and the crosslinking agent. The above-mentioned explanations regarding the type and content of the vinyl monomer, the type and content of the crosslinking agent, etc. are also referred to appropriately in the method for producing the porous body.

[0059] Specifically, the HIPE foam can be produced by carrying out an emulsification step, a polymerization step, and a drying step as described below. First, an aqueous liquid (aqueous phase) containing water is dropped into an oily liquid (organic phase) containing organic substances such as a vinyl monomer, a crosslinking agent, an emulsifier, and a polymerization initiator while stirring to prepare a water-in-oil type high internal phase emulsion (emulsification step). In the emulsification step, a high internal phase emulsion can be prepared by adding an aqueous liquid to an oily liquid so that the aqueous phase is, for example, three times or more the organic phase in volume ratio. The ratio of the aqueous phase to be contained in the organic phase can be adjusted by the weight ratio of the organic phase to the aqueous phase. The content of the aqueous phase in the high internal phase emulsion is preferably 300 to 3000 parts by weight, more preferably 400 to 2500 parts by weight, and even more preferably 500 to 2000 parts by weight, relative to 100 parts by weight of the organic phase. Next, the high internal phase emulsion is heated to polymerize the vinyl monomer, crosslinking agent, etc. in the organic phase to obtain a polymerization product (specifically, a crosslinked polymer containing water) (polymerization step). Thereafter, the polymerization product is dried to obtain a HIPE foam composed of a crosslinked polymer (drying step).

[0060] The stirring speed in the emulsification step is not particularly limited. For example, the stirring power density is 0.01 kW / m 3 ~10kW / m 3The addition rate of the aqueous liquid can be adjusted within the range of 10 wt% / min to 1000 wt% / min. The emulsification method includes, but is not limited to, a method in which the oily liquid and the aqueous liquid are added to a stirring vessel and stirring is started to emulsify the oily liquid, or a method in which only the oily liquid is added to a stirring vessel and stirring is started, and under stirring, the aqueous liquid is added to the vessel using a pump or the like to emulsify the oily liquid. When the aqueous liquid is added using a pump or the like, the addition rate of the aqueous liquid is not limited to, but can be adjusted within the range of 10 wt% / min to 1000 wt% / min to the oily liquid. Examples of the emulsification method include a batch-type emulsification process in which emulsification is performed using a stirring vessel or a centrifugal shaker equipped with a stirring device, and a continuous-type emulsification process in which the oily liquid and the aqueous liquid are continuously supplied and mixed in a line equipped with a static mixer, mesh, or the like. The emulsification method is not particularly limited.

[0061] The aqueous phase may contain water such as deionized water, a polymerization initiator, an electrolyte, etc. In the emulsification step, for example, an oily liquid and an aqueous liquid are prepared, and the aqueous liquid is added to the oily liquid under stirring to prepare a high internal phase emulsion. In the emulsification step, additives such as a flame retardant, a flame retardant auxiliary, a light resistance agent, and a colorant may be appropriately blended into the aqueous phase and / or the organic phase.

[0062] The flame retardant is used to improve the flame retardancy of the HIPE foam. Examples of the flame retardant include organic compounds containing halogen, phosphorus, nitrogen, silicone, etc.; inorganic compounds containing metal hydroxide, phosphorus, nitrogen, etc., and the flame retardant can be used within a range that does not impair the effects of the present invention. When the flame retardant is blended, the blending amount is preferably 5 to 20 parts by weight per 100 parts by weight of the total of the vinyl monomer component and the crosslinking agent component constituting the crosslinked polymer. From the viewpoint of easily imparting excellent flame retardancy even with a small amount of addition, it is preferable to use a brominated bisphenol flame retardant having a 2,3-dibromo-2-methylpropyl group and / or a brominated bisphenol flame retardant having a 2,3-dibromopropyl group, and it is even more preferable to use 2,2-bis(4-(2,3-dibromo-2-methylpropoxy)-3,5-dibromophenyl)propane. In addition, a flame retardant auxiliary can be appropriately blended into the HIPE foam in order to improve the flame retardant efficiency. For example, when a halogen-based flame retardant is used, if a radical generator such as dicumyl peroxide is used as the flame retardant auxiliary, the decomposition of the radical generator promotes the detachment of halogen from the flame retardant, and the flame retardant efficiency can be improved. When a halogen-based flame retardant is used, if an antimony compound such as antimony trioxide is used as the flame retardant auxiliary, the radical trapping effect of the halogen-based flame retardant and the air blocking effect of antimony oxide are combined synergistically, and the flame retardant efficiency can be improved. The flame retardant may be used alone, or two or more flame retardants with different flame retardant mechanisms may be used in combination.

[0063] The polymerization initiator is used to start the polymerization of vinyl monomers. As the polymerization initiator, a radical polymerization initiator can be used. Specifically, dilauroyl peroxide (LPO), di(4-t-butylcyclohexyl)peroxydicarbonate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, di(3,5,5-trimethylhexanoyl)peroxide, t-butylperoxypivalerate, t-hexylperoxypivalerate, t-butylperoxyneoheptanoate, t-butylperoxyneodecanoate, t-hexylperoxyneodecanoate, Organic peroxides such as di(2-ethylhexyl)peroxydicarbonate, 1,1,3,3-tetramethylbutylperoxyneodecanoate, and benzoyl peroxide; and azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'azobis(4-dimethylvaleronitrile), dimethyl 2,2'azobis(2-methylpropionate), and 2,2'azobis(2-methylbutyronitrile) are used. From the viewpoint of suppressing boiling of water during polymerization, the one-hour half-life temperature of the polymerization initiator is preferably 95°C or less, and more preferably 90°C or less. In addition, from the viewpoint of safety, in order to suppress decomposition of the polymerization initiator at room temperature, the one-hour half-life temperature of the polymerization initiator is preferably 50°C or more, and more preferably 55°C or more. As the polymerization initiator, one or more substances can be used. From the viewpoint of shortening the polymerization time without decreasing the uniformity of the density of the HIPE foam, it is preferable to use a combination of an organic peroxide having a one-hour half-life temperature of 50° C. or more and less than 70° C. and an organic peroxide having a one-hour half-life temperature of 70° C. or more and 90° C. or less. The polymerization initiator can be added to the organic phase and / or the aqueous phase. When the polymerization initiator is added to the aqueous phase, a water-soluble polymerization initiator such as 2,2'azobis(2-(2-imidazolin-2-yl)propane)dihydrochloride, 2,2'azobis(2-methylpropionamidine dihydrochloride, potassium persulfate, ammonium persulfate, etc. may be used. The amount of the polymerization initiator to be added can be, for example, in the range of 0.1 to 5 parts by weight per 100 parts by weight of the total of the vinyl monomer and the crosslinking agent.

[0064] The emulsifier is used for forming and stabilizing a high internal phase emulsion. For example, a surfactant can be used as the emulsifier. Specifically, glycerol esters such as polyglycerol condensed ricinoleate, polyglycerol stearate, polyglycerol oleate, polyglycerol laurate, and polyglycerol myristate; sorbitol esters such as sorbitan oleate, sorbitan stearate, sorbitan laurate, sorbitan laurate, and sorbitan palmitate; ethylene glycol sorbitan esters; ethylene glycol esters; copolymers of polyethylene glycol and polypropylene glycol, and the like, can be used. The amount of the emulsifier to be added can be, for example, in the range of 1 to 30 parts by weight per 100 parts by weight of the total of the vinyl monomer, the crosslinking agent, and the emulsifier.

[0065] The electrolyte is used to impart ionic strength to the aqueous phase and to increase the stability of the emulsion. As the electrolyte, a water-soluble electrolyte can be used. Specifically, calcium chloride, sodium chloride, magnesium chloride, sodium acetate, sodium citrate, sodium sulfate, calcium sulfate, magnesium sulfate, sodium dihydrogen phosphate, disodium hydrogen phosphate, etc. can be used. The amount of the electrolyte added can be, for example, in the range of 0.01 to 10 parts by weight with respect to 100 parts by weight of the aqueous liquid.

[0066] The polymerization temperature in the polymerization step is adjusted depending on, for example, the type of vinyl polymer, the type of polymerization initiator, the type of crosslinking agent, etc. The polymerization temperature is, for example, 50°C to 90°C.

[0067] In the drying process, the crosslinked polymer containing water is dried using an oven, a vacuum dryer, a high-frequency / microwave dryer, or the like. When the drying is completed, the places where water droplets were present in the emulsion before polymerization become bubbles in the polymer after drying, and a porous body can be obtained. Before drying, the crosslinked polymer can be dehydrated by squeezing it using, for example, a press machine. The squeezing can be performed at room temperature (for example, 23°C), but can also be performed at a temperature above the glass transition temperature of the crosslinked polymer that constitutes the HIPE foam. In this case, dehydration by squeezing becomes easier, and the drying time can be shortened. The crosslinked polymer can also be dehydrated by centrifugation. In this case, the drying time is also shortened. EXAMPLES

[0068] Examples and comparative examples of porous bodies (specifically, HIPE foams) are described below. In these examples, the HIPE foams shown in the examples in Tables 2 and 3 and the comparative examples in Table 4 were produced by the following method. Note that the specific aspects of the HIPE foams according to the present invention are not limited to the aspects of the examples shown below, and the configurations can be appropriately changed without departing from the gist of the present invention. Note that "%" in the examples means % by weight.

[0069] [Example 1] First, in a glass container with an internal volume of 3 L and equipped with a stirrer with a torque converter, 31 g of styrene and 47.5 g of butyl acrylate as vinyl monomers, 4 g of divinylbenzene with a purity of 57% as a hard crosslinking agent (hereinafter referred to as the first crosslinking agent) (2.3 g as divinylbenzene), 10 g of polyethylene glycol diacrylate (specifically, NK Ester A-400 / purity 95% manufactured by Shin-Nakamura Chemical Co., Ltd.) as a soft crosslinking agent (hereinafter referred to as the second crosslinking agent) (9.5 g as polyethylene glycol diacrylate), 7.5 g of polyglycerin condensed ricinoleate (specifically, CRS-75 manufactured by Sakamoto Yakuhin Kogyo Co., Ltd.) as an emulsifier, and 1 g of dilauroyl peroxide as a polymerization initiator were added. These were mixed in the glass container to form an organic phase.

[0070] Stirring power density 1.1kW / m 3 While stirring the organic phase at 450 g / min, 900 g of deionized water was added at a rate of about 450 g / min. Stirring was continued for 10 minutes after the addition of deionized water was completed to prepare a water-in-oil (i.e., W / O) high internal phase emulsion. The stirring power density after emulsification was 1.0 kW / m 3 The stirring power density (kW / m 3 ) is calculated from the torque (N m) and rotation speed (rpm) of the mixing device, and the power (kW) is calculated from the volume of the contents (m 3 ) can be calculated by dividing it by

[0071] Next, the stirring power density was set to 0.1 kW / m 3 The pressure in the glass container was reduced by connecting an aspirator to the container to remove the microbubbles contained in the emulsion. Ten minutes after the start of the reduction in pressure, the stirring was stopped and the pressure in the container was returned to atmospheric pressure.

[0072] The contents of the glass container were filled into a container having a length of about 250 mm, a width of about 180 mm, and a depth of about 90 mm, and polymerized in an oven at 70° C. for about 18 hours to obtain a water-containing HIPE foam. The HIPE foam was removed from the oven and cooled to room temperature.

[0073] After cooling, the HIPE foam was taken out of the container, washed with water, dehydrated, and dried in an oven at 85°C until it reached a constant weight. In this way, a rectangular HIPE foam (specifically, an impact absorbing material) made of a vinyl cross-linked polymer was obtained. The apparent density of this HIPE foam was 94 g / L (i.e., 94 kg / m 3 ) was.

[0074] The composition of the crosslinked polymer is shown in Table 2. The contents of the various components (vinyl monomer and crosslinking agent) in the crosslinked polymer can be calculated from the blending amounts of the various components (in the case of the crosslinking agent, the blending amount excluding impurities) and the total blending amount of the vinyl monomer component and the crosslinking agent component (excluding impurities) at the time of blending. In the tables, the compound names are abbreviated as follows: St: styrene BA: Butyl acrylate DVB: Divinylbenzene PEGDA: Polyethylene glycol diacrylate EpDA: Epoxy diacrylate (specifically, epoxy prepolymer modified with acrylic at both ends) PGPR: Polyglycerol condensed ricinoleate LPO: Dilauryl peroxide

[0075] [Examples 2 to 11, Comparative Examples 1 to 6] A HIPE foam was produced in the same manner as in Example 1, except that the charged composition was changed as shown in Tables 2 to 4. In addition, the changes other than the feed composition were as follows: In Example 2, the stirring power density in the emulsification process was changed to 1.6 kW / m 3 In Examples 3 and 8 and Comparative Example 1, the stirring power density in the emulsification step was changed to 0.7 kW / m 3 In Example 9, the stirring power density in the emulsification step was changed to 7.8 kW / m 3 In Example 10, the stirring power density in the emulsification step and the defoaming step was changed to 0.03 kW / m 3 was changed to.

[0076] [evaluation] The following measurements and evaluations were carried out for Examples 1 to 11 and Comparative Examples 1 to 6. The results are shown in Tables 2 to 6.

[0077] (apparent density:ρ) Three test pieces without a skin layer of a specified size (specifically, thickness: 25 mm, width: 50 mm, length: 50 mm) were cut out from the HIPE foam produced as described above so as to include the center of the HIPE foam. Then, the weight and actual dimensions (specifically, volume) of the test pieces were measured. The weight of the test piece was divided by the volume to calculate the apparent density of the test piece, and the arithmetic average value of the apparent densities of the three test pieces was taken as the apparent density ρ of the HIPE foam.

[0078] (Glass transition temperature: Tg) Based on JIS K7121:1987, Tg was calculated by differential scanning calorimetry (i.e., DSC) analysis. As a measuring device, DSC250 manufactured by TA Instruments Japan Co., Ltd. was used. Specifically, first, a test piece of about 2 mg was taken from near the center of the HIPE foam. As a condition adjustment of the test piece, "(3) A case where the glass transition temperature is measured after a certain heat treatment" was adopted. Specifically, the taken test piece was left to stand for 24 hours or more in a constant temperature and humidity room at a temperature of 23°C and a humidity of 50%. Next, the test piece was heated at a heating rate of 10°C / min to a temperature about 30°C higher than the temperature at the end of the glass transition, and was kept at this temperature for 10 minutes, and then cooled at a cooling rate of 10°C / min to a temperature about 50°C lower than the glass transition temperature. For example, in the measurement of Tg of the HIPE foam of Example 1, it was heated to 40°C and then cooled to -45°C. After cooling, the temperature was maintained for 10 minutes to stabilize the apparatus, and DSC measurement was performed at a temperature rise rate of 20°C / min up to a temperature about 30°C higher than the temperature at the end of the glass transition to obtain a DSC curve. The midpoint glass transition temperature was determined from this DSC curve, and this value was taken as the glass transition temperature Tg. The measurement temperature range in Examples 1 to 11 and Comparative Examples 1 to 6 was -90°C to 70°C.

[0079] (Molecular weight between crosslinking points: Mc) Three cubic test pieces with no skin layer, each measuring 10 mm x 10 mm x 10 mm, were cut out from the center of the HIPE foam. Dynamic viscoelastic analysis (DMA) was performed on these three test pieces to measure the storage modulus E' in the temperature range of -100 to 120°C. The measurement device used was a DMA7100 manufactured by Hitachi High-Tech Science Corporation. The measurement conditions were as follows: Deformation mode: Compression ·Temperature: -100~120℃ Heating rate: 10℃ / min Frequency: 1Hz Load: 10mN

[0080] Using the storage modulus E' and temperature T in the rubbery flat portion measured by dynamic viscoelastic analysis of the above three test pieces, the molecular weight between crosslinking points Mc was calculated from the following formula (I). Note that FIG. 2 shows a representative example of a DMA curve of the HIPE foam of the embodiment. The DMA curve is obtained by plotting temperature on the horizontal axis and storage modulus E' on the vertical axis. In the embodiment, the molecular weight between crosslinking points was calculated from the storage modulus E' at three temperatures randomly selected from the temperature range of Tg+50°C to Tg+80°C, which is the rubbery flat portion of the crosslinked polymer constituting the HIPE foam, and the arithmetic average value of the nine calculated molecular weights between crosslinking points was adopted as the molecular weight between crosslinking points Mc. Note that Tg is the glass transition temperature of the crosslinked polymer constituting the HIPE foam. Mc = 2(1 + μ)ρRT / E' (I) In addition, under the measurement conditions of the above dynamic viscoelastic analysis, the distortion generated in the cross-linked polymer constituting the HIPE foam is extremely small, and it can be assumed that no volume change occurs. Therefore, the storage modulus E' and the molecular weight Mc between cross-linking points were calculated under a constant volume condition, i.e., a Poisson's ratio of 0.5.

[0081] (average bubble diameter) The method for measuring the bubble diameter is as follows. Using a feather blade, samples for observation were cut out from the center of the short side and thickness direction of the rectangular parallelepiped HIPE foam, and from the center of the thickness direction at both ends of the short side. Next, the samples were observed with a low-vacuum scanning electron microscope (Miniscope (registered trademark) TM3030Plus manufactured by Hitachi High-Tech Science Corporation), and cross-sectional photographs were taken. Representative examples of cross-sectional photographs (magnification: 500 times) of the examples and comparative examples are shown in Figure 1. The detailed observation conditions were as follows. - Sample pretreatment: The sample was treated for electrical conductivity using a metal coating device (MSP-1S from Vacuum Device Co., Ltd.) Au-Pd was used as the target electrode. Magnification: 50x Acceleration voltage: 5kV Observation conditions: Surface (low magnification) Observation mode: Secondary electrons (standard)

[0082] Next, the cross-sectional photographs were analyzed using image processing software (NanoHunter NS2K-Pro from Nano Systems Co., Ltd.) to determine the average bubble diameter of each sample. The average bubble diameter of the HIPE foam was calculated by arithmetically averaging the three average bubble diameters obtained. The detailed analysis procedures and conditions were as follows: (1) Monochrome conversion (2) Smoothing filter (3x3, 8 neighborhoods, number of processes = 1) (3) Density unevenness correction (brighter than background, size = 5) (4) NS binarization (darker than background, clarity = 9, sensitivity = 1, noise removal, density range = 0 to 255) (5) Contraction (8 neighbors, number of processes = 1) (6) Image selection by feature (area) (select only 50~∞μm2, 8 neighbors) (7) Dilation without connections to neighbors (8 neighbors, number of processes = 3) (8) Measurement of circle equivalent diameter (calculated from area, 8 neighbors)

[0083] (average diameter of through holes) Cross-sectional photographs were taken in the same manner as for the bubble diameter, except that the observation magnification was changed to 500x and the observation mode was changed to backscattered electron method (standard). Next, the cross-sectional photographs were analyzed using image processing software (WinROOF2013, manufactured by Mitani Shoji Co., Ltd.) to determine the average through-hole diameter of each sample. The average diameter of the through-holes of the HIPE foam was calculated by arithmetically averaging the three average through-hole diameters obtained. The detailed analysis procedure and conditions were as follows: (1) Monochrome imaging (2) Averaging filter (filter size = 3 × 3, number of times = 1) (3) Automatic binarization (discriminant analysis method, extraction area = dark area, target density range = 0 to 255) (4) Morphology adjustment (dilation, times = 3) (5) Measurement from shape characteristics (measurement items = circle equivalent diameter, number)

[0084] (Storage modulus and storage modulus ratio at 0℃ and 23℃) From the storage modulus E' in the temperature range of -100 to 120°C measured by the dynamic viscoelastic analysis (DMA), the storage modulus at 0°C and the storage modulus at 23°C were calculated. As a representative example, the DMA curve (specifically, the storage modulus curve) of the porous body of Example 1 is shown in Figure 2. In addition, the ratio of the storage modulus at 0°C to the storage modulus at 23°C was calculated.

[0085] (Maximum value of loss tangent tanδ and half-width of tanδ peak) In the same manner as in the measurement of the molecular weight Mc between crosslinking points, the loss tangent tanδ was measured in the temperature range of -100 to 120°C. The loss tangent tanδ is the value obtained by dividing the loss modulus E" by the storage modulus E', and E', E", and tanδ can be determined simultaneously in the dynamic viscoelastic analysis. In the tanδ curve thus obtained, with the horizontal axis representing temperature T and the vertical axis representing tanδ, the maximum value on the vertical axis was taken as the maximum value of the loss tangent tanδ. In the tanδ curve, the two temperatures of the tanδ peak at the position showing half the maximum value of tanδ were determined, and the temperature difference between them was taken as the half-value width H. The DMA curve (specifically, the tanδ curve) of the porous body of Example 1 is shown in FIG. 3.

[0086] (Tensile elongation at break) Five samples measuring 4 mm thick, 50 mm long, and 180 mm wide were cut from near the center of the HIPE foam. Using a 1A-shaped (JIS K 7161-2:2014) dumbbell punch, the samples were punched into a 1A shape to obtain five test pieces. These test pieces were subjected to tensile tests under the following conditions based on JIS K 7161-2:2014 using an autograph AGS-10kNX manufactured by Shimadzu Corporation. The tensile breaking strain was calculated from the obtained load-displacement curve, and the average value of the five measurement results was taken as the tensile breaking elongation. ·Room temperature: 23℃ ·Humidity: 50% Pulling speed: 100mm / min When the tensile breaking point was 70% or more, the ductility was judged to be good, and indicated by "○" in the table. On the other hand, when the tensile breaking point was less than 70%, the ductility was judged to be poor, and indicated by "×" in the table.

[0087] (Breaking Energy) The arithmetic mean value of the energy in the region from 0% strain to the tensile fracture strain in the load-displacement curve measured by the above tensile test was calculated. The fracture energy was calculated automatically by the autograph AGS-10kNX. In addition, the breaking energy per unit weight of the HIPE foam was calculated, and when the calculated value was 50 mJ / g or more, the strength was judged to be good and indicated by "○" in the table. On the other hand, when the calculated value was less than 50 mJ / g, the strength was judged to be poor and indicated by "×" in the table.

[0088] (Recovery rate after 30 minutes and 24 hours, compression set) A test piece without a skin layer measuring 25 mm x 50 mm x 50 mm was cut out from the center of the HIPE foam, and the compression set was measured using this test piece in accordance with JIS K 6767:1999. Specifically, the test piece was compressed to a state where it was distorted 25% relative to a thickness of 25 mm in an environment of temperature: 23°C and humidity: 50%, and was left as it was for 22 hours, and then the pressure was released. The thickness was measured 30 minutes and 24 hours after the pressure was released. The recovery rate and compression set 30 minutes and 24 hours after the pressure was released were calculated from the following formula. (Restoration rate after 30 minutes) = (Thickness after 30 minutes from decompression) / (original thickness) x 100 [%] (24-hour recovery rate) = (thickness 24 hours after decompression) / (original thickness) x 100[%] (Compression set) = ((original thickness) - (thickness 24 hours after decompression)) / (original thickness) x 100[%] When the recovery rate after 30 minutes was 90% or more, the recovery was judged to be good and indicated in the table by "○". On the other hand, when the recovery rate after 30 minutes was less than 90%, the recovery was judged to be poor and indicated in the table by "×".

[0089] (Overall Judgment) When the ductility, strength, and recovery were all good, the table was marked with "○". On the other hand, when any one of them was poor, the table was marked with "×". [Table 2]

[0090] [Table 3]

[0091] [Table 4]

[0092] As can be seen from Tables 2 to 4, the HIPE foams of the examples are flexible and have excellent ductility, as well as excellent recovery and strength.

[0093] Comparative Example 1 is an example in which the apparent density was large and the ductility was insufficient.

[0094] Comparative Examples 2 and 3 are examples in which the molecular weight between crosslinks is small, and the ductility is insufficient. Comparative Example 4 is an example in which the molecular weight between crosslinking points is large, and the recovery property was insufficient.

[0095] Comparative Example 5 is an example in which the glass transition temperature was low, and the ductility and strength were insufficient. Comparative Example 6 , revenge The originality was insufficient. [Explanation of symbols]

[0096] 1 Porous body 11 Cross-linked polymers 12 Bubble Wall 13 Bubbles 14 Through hole

Claims

1. A porous body having a base resin that is a crosslinked polymer obtained by crosslinking a polymer of an acrylic monomer and / or a styrene monomer as a vinyl monomer, The polymer is a polymer of the vinyl monomer having an acrylic monomer content of 40% by weight or more, The storage modulus of the porous body at 23° C. is 10 kPa or more and 500 kPa or less, The apparent density of the porous body is 20 kg / m 3 More than 250kg / m 3 is as follows: The crosslinked polymer has a glass transition temperature of −30° C. or higher, The molecular weight between crosslinking points of the crosslinked polymer is 1.0×10 4 Above 12 x 10 4 The porous body is as follows:

2. The porous body according to claim 1, wherein the maximum value of the loss tangent tanδ in a temperature-loss tangent tanδ curve measured by performing dynamic viscoelasticity measurement on the porous body under the conditions of a frequency of 1 Hz, a load of 10 mN, and a deformation mode of compression is 0.8 or more and 1.6 or less.

3. The porous body according to claim 1 or 2, wherein the half-width of a tan δ peak indicating the maximum value of the loss tangent tan δ in a temperature-loss tangent tan δ curve measured by performing dynamic viscoelasticity measurement on the porous body under the conditions of a frequency of 1 Hz, a load of 10 mN, and a deformation mode of compression is 10° C. or more and 25° C. or less.

4. the crosslinked polymer is obtained by crosslinking a copolymer of the acrylic monomer and the styrene monomer, 4. The porous body according to claim 1, wherein the acrylic monomer is an ester of (meth)acrylic acid and an alcohol having 1 to 20 carbon atoms.

5. The crosslinked polymer is a porous body according to any one of claims 1 to 4, which is obtained by crosslinking a polymer of the acrylic monomer and / or the styrene monomer with a first crosslinking agent having a functional group equivalent of 130 g / eq or less and a second crosslinking agent having a functional group equivalent of more than 130 g / eq and 5000 g / eq or less.

6. The crosslinked polymer is obtained by crosslinking a polymer of the acrylic monomer and / or the styrene monomer with a crosslinking agent having a functional group equivalent of 500 g / eq or more and 3000 g / eq or less, and the crosslinking agent is a urethane (meth)acrylate and / or an epoxy (meth)acrylate, according to any one of claims 1 to 4.

7. 7. The porous body according to claim 1, which has a restoration rate of 90% or more 30 minutes after compression of the porous body by 25% at 23° C. and decompression.

8. The porous body according to any one of claims 1 to 7, wherein the porous body has a tensile elongation at break at 23°C of 70% or more.

9. The porous body according to any one of claims 1 to 8, wherein the porous body has a breaking energy per unit weight of 50 mJ / g or more.

Citation Information

Patent Citations

  • Absorbent foams made from high internal phase emulsions useful for acquiring and distributing aqueous fluids

    JP1999503177A

  • Foam materials obtained from high internal phase emulsions

    JP2003514052A

  • Rapid preparation of foaming materials from high-internal-phase emulsions

    JP2004529212A

  • Production method for foam

    JP2012051984A

  • Latex compositions and uses thereof

    US20120214916A1